2004
DOI: 10.1016/j.femsle.2004.10.020
|View full text |Cite
|
Sign up to set email alerts
|

TheSaccharomyces cerevisiaegeneECM11is a positive effector of meiosis

Abstract: Ecm11 is classified as a protein involved in yeast cell wall biogenesis and organization, but in this paper, we provide evidence that it is involved in meiosis as well. Mutants with deleted ECM11 exhibit complex defects in meiosis: replication, recombination and chromosome segregation are affected. The ecm11Delta diploid strains sporulate more slowly and less efficiently than parental strains with wild type copies of ECM11. Fluorescence activated cell sorter scans of DNA content during sporulation showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
2
14
2
Order By: Relevance
“…Drosophila females have only a single known CE protein, Corona, which is also known as Cona (170). In S. cerevisiae , appropriate installation of the TF protein, Zip1, is dependent on the presence of the CE proteins Ecm11 and Gmc2 (100, 237) and, more specifically, requires the SUMOylation of Ecm11 in a Gmc2-dependent manner (224, 236). Indeed, SUMO appears to be an integral component of the SC in many organisms and is required for initial loading of Zip1 (reviewed by 242).…”
Section: Initiation Of Synapsis and Recombinationmentioning
confidence: 99%
“…Drosophila females have only a single known CE protein, Corona, which is also known as Cona (170). In S. cerevisiae , appropriate installation of the TF protein, Zip1, is dependent on the presence of the CE proteins Ecm11 and Gmc2 (100, 237) and, more specifically, requires the SUMOylation of Ecm11 in a Gmc2-dependent manner (224, 236). Indeed, SUMO appears to be an integral component of the SC in many organisms and is required for initial loading of Zip1 (reviewed by 242).…”
Section: Initiation Of Synapsis and Recombinationmentioning
confidence: 99%
“…These regulated events are expected to use meiosis-specific regulators and this was the supposed role of Ecm11. In our previous work we have demonstrated that Ecm11 is indeed required in meiosis (Zavec et al, 2004). Mutants ecm11 exhibit complex defects in meiotic replication and recombination: diminished meiotic DNA synthesis, reduced crossing over, increased gene conversion events and reduced levels of sporulation and spore viability (Fig.…”
Section: Ecm11 Yeast Protein With a Role In Replication And Recombinmentioning
confidence: 94%
“…In the parental strain, 98% of spores germinated after dissection, while only 50% spores of the ecm11 mutants survived. Beside strongly reduced spore viability in the ecm11 mutants, a strongly elevated fraction of tetrads exhibiting two viable spores in ecm11 mutants was observed (Zavec et al, 2004). The majority of ecm11 asci (56%) produced only two viable spores, while only 1% of such asci were observed in the parental strain.…”
Section: Ecm11 Is Required For Crossing Over But Not For Gene Convermentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, a number of sumoylation events occur during the early stages of meiosis and these are important for premeiotic DNA replication, recombination and crossing over [31][32][33]. Rather than occurring confluently along the meiotic chromosomes, they would be expected to be situated at discrete genomic sites of on-going double-strand break repair [34].…”
Section: Sumo-dependent Recombination In Yeast: Sumo Localizes To Aximentioning
confidence: 99%